T42. JUMPING TO CONCLUSIONS IS ASSOCIATED WITH THE POLYGENIC RISK SCORE FOR INTELLIGENCE BUT NOT FOR SCHIZOPHRENIA. PRELIMINARY FINDINGS FROM THE EU-GEI STUDY. (9th April 2019) - Tripoli, Giada; Quattrone, Diego; Murray, Graham; Gayer-Anderson, Charlotte; Rodriguez, Victoria; Ferraro, Laura; Cascia, Caterina La; Sartorio, Crocettarachele; Seminerio, Fabio; Barbera, Daniele La; Morgan, Craig; Sham, Pak; et al.
Abstract: Background: Psychotic patients tend to require less evidence to make decisions compared to general population. This bias named Jumping to Conclusions (JTC) has been found at First Episode Psychosis (FEP) in schizophrenia patients and associated with proneness to psychotic-like experiences in the general population. Interesting findings showed also strong association with lower cognitive functioning in psychotic patients, which in turn has been shown as a candidate intermediate phenotype for psychosis. Overall, findings to date could suggest a shared genetic liability between the occurrence of JTC and psychosis, potentially via IQ. The present study aims to investigate whether the presence of JTC bias might be explained by Schizophrenia (SZ) and IQ Polygenic Risk Scores (PRSs) in a sample of FEP and healthy controls. Methods: We analysed data on JTC (Beads task 60:40, N. of beads) in a sample of 519 FEP and 881 population controls for which genetic information was available, recruited as part as the EU-GEI study across UK, Netherlands, France, Spain, Italy and Brazil. SZ PRS and IQ PRS were built using the results from large mega-analyses from Working Groups of the Psychiatric Genomics Consortium and Savage et al. (2018) respectively. In PRSice, individuals' number of risk alleles in the target sample was weighted by the log odds ratio from the discovery samples and summed into the PRS at a 0.05 SNPs Pt-threshold (apriori selected) for SZ PRS and at the best SNPs Pt-threshold for IQ PRS. We excluded people of homogeneous African ancestry. In STATA, linear regression models were used to firstly test whether JTC was affected by the case/control status alone. In a second step, we further tested the effects on JTC of: 1) PRS for SZ; and 2) PRS for IQ. These models were adjusted for age, gender, and 20 principal components for population stratification. Results: JTC was associated with case status (B=-0.87, 95% CI -1.35 to -0.39, p<0.001) and this model explained 7% of the variance. SZ PRS was not associated with jumping to conclusions (B= 0.43, 95% CI -0.25 to 1.09, p=0.21); whereas IQ PRS (B=0.51, 95% CI 0.26 to 0.76, p<0.001) significantly predicted the number of beads drawn. When adding the IQ PRS the variance explained raised to 10%, of which 1% due to the putative PRS effect. Discussion: Preliminary findings suggest that the tendency to jump to conclusions cannot be explained by schizophrenia genetic underpinnings using polygenic risk score strategy. Moreover, these preliminary results identified an interesting association between genetics for general intelligence and the JTC bias. Therefore, further investigation is warranted to explore the genetic association between JTC and psychosis as potentially mediated by the underlying genetic basis of IQ, rather than being influenced by the genetics of psychosis directly.